Short Communication: New distributional records of Sonneratia spp. from Andaman and Nicobar Islands, India - PADISAMY RAGAVAN; K. RAVICHANDRAN; P. M. MOHAN; ALOK SXAENA; R. S. PRASANTH; R. S.C. JAYARAJ; S. SARAVANAN (Society for Indonesian Biodiversity, 2014)
Ragavan P, Ravichandran K, Mohan PM, Sxaena A, Prasanth R S, Jayaraj RSC, Saravanan S. 2014. New distributional records of Sonneratia spp. from Andaman and Nicobar Islands, India. Biodiversitas 15: 251-260. Sonneratia lanceolata, Sonneratia x urama andSonneratia x gulngai was collected from Great Nicobar Island, which representing a new addition to the mangrove flora of India. S.lanceolata is distinguished from S. caseolaris by its drooping branches, lanceolate leaves and ovoidal bud without medial constriction.S. x urama and S. x gulngai are putative hybrids. S. x urama is putative hybrid between S. alba and S. lanceolata, whereas S. x gulngai is putative hybrid between S. alba and S. caseolaris. A detailed description along with colour plate and relevant notes is provided for further collection and identification of these species in the field.